Isu Dan Masalah Dalam Analisis Kebijakan Pendidikan Di MAS PAB 1 Sampali - Ahamad Mukhlasin; Anti Anisa; Eliza Putri; Rio Febriyan; Suci Ramadani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research discusses several educational problems at MAS PAB I Sampali and analyzes policies that can be implemented to improve the quality of education. The main focus of research includes curriculum, educational infrastructure, parental involvement, and policy implementation challenges. First, inappropriate curricula are a concern, requiring thorough evaluation and adjustments to include 21st century skills. Second, limited educational infrastructure requires evaluation and improvement to ensure the availability of facilities that are conducive to effective learning. Third, low parental involvement can be overcome through special programs such as regular meetings and parent training. Fourth, policy implementation challenges, such as resistance to change, require identification of barriers and effective implementation strategies. This solution can be the basis for improving the quality of education at MAS PAB I Sampali and making it more responsive to today's demands. This transformation is not only to meet current educational needs but also to face future challenges with confidence and readiness.